Audit and feedback in cardio– and cerebrovascular setting: Toward a path of high reliability in Italian healthcare - Ciurleo, Rosella; De Cola, Maria Cristina; Agabiti, Nera; Di Martino, Mirko; Bramanti, Placido; Corallo, Francesco (Frontiers in Public Health, 2022)
Adopting audit and feedback (A&F) strategies could be a suitable healthcare intervention to fulfill the challenge of monitoring and improving clinical guidelines in evidence-based medicine. Indeed, A&F is used to encourage professionals to better adhere to standard guidelines to improve healthcare performance. Briefly, an audit is an inspection of professional practice in comparison to professional standards or targets whose results are subsequently communicated to professionals in a structured manner. Although A&F strategies have been adopted in several time-dependent settings, such as for acute myocardial infarction (AMI) and stroke, interest of audits in rehabilitation care is also emerging. Recently, the Italian Ministry of Health has funded a national network project called EASY-NET, whose main objective is to evaluate the effectiveness of A&F strategies to improve healthcare practice and equity in various clinical and organizational settings in seven Italian regions. Last but not the least of these regions is the Sicily, represented within the project by the IRCCS Centro Neurolesi Bonino-Pulejo of Messina as the work package 7 (WP7). The EASY-NET WP7 is focused on the effectiveness of A&F strategies in both AMI and ischemic stroke setting, from acute to rehabilitation process of care. In this study, we described the study protocol, including the study design and methodology, providing a detailed description of the new model of A&F based on telemedicine, and discussing the possible challenges of this project.